2010
DOI: 10.4049/jimmunol.1001857
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Activation Limits Airway Branching through Inhibition of Sp1-Mediated Fibroblast Growth Factor-10 Expression

Abstract: Bronchopulmonary dysplasia (BPD) is a frequent complication of preterm birth. This chronic lung disease results from arrested saccular airway development and is most common in infants exposed to inflammatory stimuli. In experimental models, inflammation inhibits expression of fibroblast growth factor-10 (FGF-10) and impairs epithelial–mesenchymal interactions during lung development; however, the mechanisms connecting inflammatory signaling with reduced growth factor expression are not yet understood. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 41 publications
4
72
0
Order By: Relevance
“…Although the connections between inflammatory signals and altered development have long been suggested, the mechanisms linking immunity and development have been less clear. Within the developing lung mesenchyme, microbial products and cytokines activate NF-B and inhibit FGF-10 expression and prevent normal epithelial-mesenchymal interactions during airway formation (8,13). Our results here reveal a novel mechanism linking inflammation-mediated NF-B activation and abnormal transcriptional regulation of Fgf-10.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although the connections between inflammatory signals and altered development have long been suggested, the mechanisms linking immunity and development have been less clear. Within the developing lung mesenchyme, microbial products and cytokines activate NF-B and inhibit FGF-10 expression and prevent normal epithelial-mesenchymal interactions during airway formation (8,13). Our results here reveal a novel mechanism linking inflammation-mediated NF-B activation and abnormal transcriptional regulation of Fgf-10.…”
Section: Discussionmentioning
confidence: 71%
“…The related Sp family member SP3 can act as both a transcriptional activator and repressor, depending on cellular context (25). We previously showed that SP1 drives FGF-10 transcription and that this effect can be inhibited by NF-B activation (8). However, it was not clear how NF-B might inhibit SP1-mediated transcription in the absence of conserved predicted NF-B binding sites.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, the inflammatory activation of macrophages during development not only contributes to tissue damage and disruption of organ development through pro-inflammatory injury, but may also skew macrophages away from their trophic functions. 111,139,140 Inflammatory activation of fetal lung macrophages through NF-κB signaling was found to upregulate proinflammatory mediators such as IL-1β and alter expression of Wnt7b, bone morphogenic protein (BMP)4 111 and fibroblast growth factor (FGF)-10. 139 And while inflammatory challenges such as lipopolysaccharide (LPS) or IL-1β administration in models of chorioamnionitis promote accelerated maturation, the mechanism is distinct from alveolarisation, characterized by a lung pathology associated with BPD.…”
Section: Csf-1 and Macrophage Manipulation In Developmentmentioning
confidence: 99%
“…111,139,140 Inflammatory activation of fetal lung macrophages through NF-κB signaling was found to upregulate proinflammatory mediators such as IL-1β and alter expression of Wnt7b, bone morphogenic protein (BMP)4 111 and fibroblast growth factor (FGF)-10. 139 And while inflammatory challenges such as lipopolysaccharide (LPS) or IL-1β administration in models of chorioamnionitis promote accelerated maturation, the mechanism is distinct from alveolarisation, characterized by a lung pathology associated with BPD. 141 Today, corticosteroids remain one of the most important advancements in reducing the mortality associated with preterm birth, however they are associated with precocious maturation and significant side effects.…”
Section: Csf-1 and Macrophage Manipulation In Developmentmentioning
confidence: 99%